Pengaruh Faktor Keuangan dan Karakteristik Pemerintah Daerah Terhadap Financial Distress (Studi Empiris Kabupaten/Kota di Provinsi Aceh Tahun 2015-2019) - Rahima Zakia; Mia Angelina Setiawan (Universitas Negeri Padang, 2021)
This study is a quantitative research that aims to obtain empirical evidence about the influence of financial factors (effectiveness ratio, efficiency ratio, solvency ratio and growth ratio) and characteristics of local government (decentralization degree, complexity of local government, area size and audit opinion) on local government financial distress in districts and cities in Aceh Province for the period 2015-2019 for 5 years. The data was obtained from the BPK and BPS. This research used a total sampling method with total sample of 23 districts / cities and used binary logistic regression analysis for analysis of the data. The value of desentralization degree and complexity of local government has a negative and significant effect on financial distress and the value of growth ratio has a positive and significant effect on financial distress. While the value of solvency ratio and area size has no significant effect and positive on financial distress and the value of effectiveness ratio, efficiency ratio and audit opinion has no significant effect and negative on financial distress.